Conversion of palm oil into biodiesel production with heterogeneous catalyst derived from spent coffee grounds ash: Process optimization through response surface methodology - Jitjamnong, Jakkrapong; Numwong, Natthida; Chuaykarn, Narinphop; Direksilp, Chatrawee; Luengnaruemitchai, Apanee; Kongrit, Napaphat; Khantikulanon, Nonlapan (My University, 2021)
In the present study, the calcination of spent coffee grounds (SCG) supporting potassium hydroxide and potassium carbonate (K2CO3) was used as a novel solid heterogeneous catalyst to convert palm oil to fatty acid methyl ester. The response surface method based on Box Behnken experimental design was used to optimize the biodiesel yield. The prepared catalyst was characterized by scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDS), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) analyses. EDS analysis of the synthesis catalyst exhibited the presence of active potassium species for high catalytic activity. The 30K/SCG–600 catalysts exhibited the highest catalytic activity and were rich in K that formed a basic heterogeneous catalyst and the highest total basicity. The effects of catalyst loading (4.5–5.5 wt.%), methanol to oil molar ratio (6:1–12:1), and reaction time (60–120 min) on the transesterification were investigated. The results showed that the predicted optimum response for biodiesel yield from RSM was 97.01%, which could be obtained using methanol: oil molar ratio of 6.68:1, catalyst loading of 4.94 wt.%, and reaction time at 82.42 min. The actual biodiesel conversion of 97.08% was achieved under the predicted optimal conditions. The results of various statistics employed with high R2 (95.07%) and R2adj (88.73%) values indicated that the predicted and actual biodiesel yield was accurate and reliable.
Keywords: Biodiesel; Heterogeneous catalyst; Response surface methodology (RSM); Spent coffee grounds; Transesterification